Susceptibility of intra- and extracellular Mycobacterium avium-intracellulare to cephem antibiotics. - Nozawa, R T (1985)
Intra- and extracellular susceptibility of 35 clinically isolated Mycobacterium avium-intracellulare strains to cefotaxime (CTX), ceftizoxime (CZX), and cefoperazone was studied. MICs for 50% of the isolates in vitro were 6.25 micrograms/ml for CTX and CZX and 25 micrograms/ml for cefoperazone. A strain susceptible to CTX (MIC, 0.78 micrograms/ml) and CZX (MIC, 1.56 micrograms/ml) infected human peripheral blood mononuclear cells in the presence of 20% autologous plasma. The mycobacteria replicated exclusively in monocytes under the above culture condition. Concentrations of CZX 1- to 16-fold higher than its in vitro MIC had little effect on intracellular replication of the strain. A concentration of CTX 16-fold higher than its in vitro MIC was bacteriostatic to the mycobacteria, but CTX of lower concentrations showed no effect on intracellular replication. Thus, ineffectiveness of the cephems on the therapy of M. avium-intracellulare infection was suggested.